Morphology and phylogenetic affinity of Chara hanii, nom. nov. (Charophyceae, Characeae) from Xinjiang, China - Romanov, Roman E.; Nikulin, Vyacheslav Yu.; Nikulin, Arthur Yu.; Zhakova, Liubov V.; Gontcharov, Andrey A. (Phytotaxa, 2026)
The extant species Chara sinkiangensis F.S. Han & P.C. Tuan in Han et al. (1978) is a homonym of the name of the fossil species C. sinkiangensis Lu (1944). Hence, the former name was replaced here with C. hanii, nom. nov., honoring one of its authors, Han Fu-Shan, a prominent Chinese charophytologist. For this species, only male plants were known from one location in Xinjiang. Examination of specimens collected during Chinese-Soviet expeditions to Xinjiang, People’s Republic of China, during 1957–1959 and stored in the Komarov Botanical Institute of the Russian Academy of Sciences revealed an isotype of C. sinkiangensis. A study of this specimen provided new data improving the description of the species. According to morphological traits, C. hanii belongs to the section Chara and could be attributed to either subsection Chara or subsection Hartmania. Phylogenetic analyses based on chloroplast gene rbcL placed this species to the subsection Hartmania, making it the third dioecious species in the subsection.